Transformasi Pendidikan: Memperkuat Kecerdasan Sosial dan Emosional Anak di Era Disrupsi - Cannavaro, Juliano; Asbari, Masduki; Nurmayanti, Rini (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this study is to explore the extent to which the world of education has been transformed due to the impact of COVID-19. It can be seen the importance of developing social and emotional intelligence in children through social interaction and play-centered learning, in this context emphasizing the need to consider learning methods. Encourage analysis and creativity, not just memorization. The research methods used in this transcript are descriptive and narrative approaches that highlight the importance of social interaction, play, and sensory and motor development in children's learning processes. The source of the data obtained listened to an oral narrative from a Youtube channel entitled "Education, Disruption and Collaboration" presented by Prof. Rhenald Kasali Ph.D an Academic and Business Practitioner. The results show that learning approaches that emphasize social and emotional intelligence and higher-order thinking skills will bring long-term benefits to children's future, the importance of collaboration in the development of education shows that adapting learning methods to the times, allows children to develop abilities that are relevant to future demands. Thus, the results of this study show that changes in education need to focus on developing life skills that prepare children for the challenges they will face in the future